2018
DOI: 10.1038/s41467-018-03962-x
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β induces miR-100 and miR-125b but blocks let-7a through LIN28B controlling PDAC progression

Abstract: TGF-β/Activin induces epithelial-to-mesenchymal transition and stemness in pancreatic ductal adenocarcinoma (PDAC). However, the microRNAs (miRNAs) regulated during this response have remained yet undetermined. Here, we show that TGF-β transcriptionally induces MIR100HG lncRNA, containing miR-100, miR-125b and let-7a in its intron, via SMAD2/3. Interestingly, we find that although the pro-tumourigenic miR-100 and miR-125b accordingly increase, the amount of anti-tumourigenic let-7a is unchanged, as TGF-β also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 51 publications
4
103
0
2
Order By: Relevance
“…Similarly, miR-155 and miR-1246 have been shown to contribute to gemcitabine resistance and were identified as potential prognostic markers in PDAC [30,31]. MiR-125b and members of the miR-99 family consisting of miRs 99a, 99b, and 100 have also been attributed oncogenic functions, regulating PDAC progression and serving as prognostic markers and predictors of chemo-responsiveness [13,32]. Conversely, miRs 34a, 148a, 200a, 200b, and 200c function as tumor-suppressive miRs in PDAC with prognostic impact that predominantly inhibit EMT, a process closely related to metastatic dissemination [14,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, miR-155 and miR-1246 have been shown to contribute to gemcitabine resistance and were identified as potential prognostic markers in PDAC [30,31]. MiR-125b and members of the miR-99 family consisting of miRs 99a, 99b, and 100 have also been attributed oncogenic functions, regulating PDAC progression and serving as prognostic markers and predictors of chemo-responsiveness [13,32]. Conversely, miRs 34a, 148a, 200a, 200b, and 200c function as tumor-suppressive miRs in PDAC with prognostic impact that predominantly inhibit EMT, a process closely related to metastatic dissemination [14,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer, particularly the pancreatic ductal adenocarcinoma (PDAC), is one of deadliest human cancers, comprising about 90% of all pancreatic cancers, and is associated with mortality and a low survival rate below 5% despite the advancement in available therapeutic options [169]. Recently, it has been demonstrated that expression of miR-100 and miR-125b in PDAC by TGF-β signaling to target similar signaling pathways co-operate to promote stemness and associated carcinogenesis, including EMT, and further reported that knockdown or suppression of miR-125b or miR-100 compromise the potential of TGF-β to induce cell migration and carcinogenesis in PDAC [104]. PRDM14, a transcriptional regulator that maintains pluripotency in embryonic stem cells, is overexpressed in pancreatic cancer tissues, and the inhibition of PRDM14 reduces sphere formation, stemness, stem cell markers, tumorigenesis, and metastasis in mice by upregulation of different miRNAs such as miR-125a-3p.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…In pancreatic ductal adenocarcinoma (PDAC), TGF‐β induces the mir‐100‐let‐7a‐2‐mir‐125b‐1 cluster host gene ( MIR100HG ), a lncRNA that gives rise to mir‐100 , let‐7a‐2 , and mir‐125b‐1 miRNAs. miR‐100 and miR‐125b promote PDAC progression and EMT, by downregulating p53 and apoptotic pathways and upregulating the pro‐survival phosphatidylinositol 3´‐kinase/Akt signaling pathway 30 . In colorectal cancer, the taurine up‐regulated gene 1 ( TUG1 ) lncRNA is a mediator of TGF‐β‐induced EMT in vitro and metastasis in vivo; TUG1 is enhanced in response to TGF‐β, in order to increase Twist1 expression, resulting in enhanced migration, invasion, and lung metastasis 31 …”
Section: Lncrnas Act As Effectors Of Tgf‐β Signalingmentioning
confidence: 99%